Policies for swapping MPI processes - Sievert, O.; Casanova, H. (High Performance Distributed Computing, 2003. Proceedings. 12th IEEE International Symposium on, 2003)
Despite the enormous amount of research and development work in the area of parallel computing, it is a common observation that simultaneous performance and ease-of-use are elusive. We believe that ease-of-use is critical for many end users, and thus seek performance enhancing techniques that can be easily retrofitted to existing parallel applications. In a precious paper we have presented MPI (message passing interface) process swapping, a simple add-on to the MPI programming environment that can improve performance in shared computing environments. MPI process swapping requires as few as three lines of source code change to an existing application. In this paper we explore a question that we had left open in our previous work: based on which policies should processes be swapped for best performance? Our results show that, with adequate swapping policies, MPI process swapping can provide substantial performance benefits with very limited implementation effort.